2021
DOI: 10.3389/fsoc.2021.637671
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Evaluation of Rapid Weight Loss in Wrestling and Taekwondo

Abstract: The practice of strategies for rapid weight loss (RWL) involve diverse factors, such as individual expectations, social interactions, structural elements, etc., conforming to a “culture” of RWL, which must be evaluated and understood in a broad sense. Based on the need of a comprehensive evaluation of the use of RWL in practitioners of combat sports, an ad hoc questionnaire designed for this study, which includes the types and detailed descriptions of RWL strategies, that athletes currently use, the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…The most frequently selected concussion symptoms comprised the same responses as WC, in addition to headaches, head pressure, and neck pain (Figure 3). These findings are in accordance with the previous literature, 18,26–28 indicating that RWL through dehydration increases concussion-related symptoms. The possible reasons for feelings of weakness and fatigue could relate to perturbations in ionic balance to restore osmotic equilibrium 29 and subsequent alterations to cell excitability and excitation–contraction coupling capabilities.…”
Section: Discussionsupporting
confidence: 94%
“…The most frequently selected concussion symptoms comprised the same responses as WC, in addition to headaches, head pressure, and neck pain (Figure 3). These findings are in accordance with the previous literature, 18,26–28 indicating that RWL through dehydration increases concussion-related symptoms. The possible reasons for feelings of weakness and fatigue could relate to perturbations in ionic balance to restore osmotic equilibrium 29 and subsequent alterations to cell excitability and excitation–contraction coupling capabilities.…”
Section: Discussionsupporting
confidence: 94%
“…Also, in some combat sports, weight reduction negatively affects the level of fatigue, tension, and total mood disturbance before competition [ 40 , 41 ]. On the other hand, vigor was inversely associated with the application of rapid weight loss [ 42 ]. The literature presented that weight loss increases the total mood disturbance of senior and junior judo athletes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are contradictory results on the influence of anger on athlete performance. Páez-Ardila et al [ 34 ] showed that judokas with increased anger were those who were defeated, while higher levels of anger improved the chances of better performance in individual and team sports [ 42 , 43 ]. Furthermore, the vigor deficit reduces the probability of winning [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eligible articles had to be conducted in Official Olympic combats with weight classes: judo, wrestling, taekwondo, or boxing athletes, practicing an RWL method. The participant’s extent of weight loss had to be ∼5% of their body weight, and only male participants >18 years of age were selected ( Khodaee et al, 2015 ; Sagayama et al, 2019 ; Lakicevic et al, 2020 ; Castor-Praga et al, 2021 ). There was no upper age limit for the participants.…”
Section: Methodsmentioning
confidence: 99%